Key Insights and Priorities for Evaluating the Effectiveness of Clinical Ethics Consultation - Honan, Lauren; Heesters, Ann; Bianchi, Andria; Salis, Marina; Bell, Jennifer (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
During the 2023 Canadian Bioethics Society forum, 28 practicing healthcare ethicists (PHEs) and other attendees from across Canada, including bioethics students and fellows, gathered virtually for a collaborative workshop entitled “Towards Evaluating Clinical Ethics Consultation Effectiveness: Engagement in a Scoping Review of Reported Outcomes”. The workshop was open to all members of the bioethics community who registered for the forum but was designed primarily for PHEs.